Analysis of the Effectiveness of Public Services Based on Patent Application - Andika, Wahyu; Ritonga, Syafruddin; Batubara, Beby Masitho (Journal La Sociale, 2025)
This study aims to analyze the effectiveness of public services based on the PATENT application in Galang District, Deli Serdang Regency. This technology-based public service is expected to increase efficiency, transparency, and accountability in the management of administrative documents. The research method used is a qualitative approach with in-depth interview, observation, and documentation techniques. The study found that PATENT applications have accelerated the process of document management, reduced transportation costs, and increased transparency of service information. However, there are still several inhibiting factors, such as limited technological infrastructure, low digital literacy among the public, technical obstacles to applications, and lack of socialization and training. People who have technological knowledge find it easier to access and use this application, while some people, especially the elderly, are experiencing difficulties. Therefore, efforts are needed to improve digital infrastructure, training for the community, and better system maintenance to increase the effectiveness of these application-based public services. The results of this study provide an overview of the challenges and opportunities in the implementation of technology in public services in the region, as well as provide recommendations to improve service quality.